Anatomical Parameters of tDCS to Modulate the Motor System after Stroke: A Review - Lefebvre, Stephanie; Liew, Sook-Lei (Frontiers in Neurology, 2017)
Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation method to modulate the local field potential in neural tissue and consequently, cortical excitability. As tDCS is relatively portable, affordable, and accessible, the applications of tDCS to probe brain-behavior connections have rapidly increased in the last ten years. One of the most promising applications is the use of tDCS to modulate excitability in the motor cortex after stroke and promote motor recovery. However, the results of clinical studies implementing tDCS to modulate motor excitability have been highly variable, with some studies demonstrating that as many as 50% or more of patients fail to show a response to stimulation. Much effort has therefore been dedicated to understanding the sources of variability affecting tDCS efficacy. Possible suspects include the placement of the electrodes, task parameters during stimulation, dosing (current amplitude, duration of stimulation, frequency of stimulation), individual states (e.g., anxiety, motivation, attention), and more. In this review, we first briefly review potential sources of variability specific to stroke motor recovery following tDCS. We then examine how the anatomical variability in tDCS placement (e.g., neural target(s) and montages employed) may alter the neuromodulatory effects that tDCS exerts on the post-stroke motor system.